Rychlá maxilární expanze a její působení na skelet maxily. Přehledový článek - Trojanová, Jaroslava; Dostálová, Taťjana; Horáček, Martin; Nocar, Adam (Ortodoncie, 2022)
The aim of our report is to present current knowledge of skeletal effects of rapid maxillary expansion (RME) focused on the maxilla and changes in its position and orientation in space (shifts and rotation). We strive to provide a complex review of conclusions of the studies available in scientific databases PubMed, Scopus, Science Direct, Google Scholar, Web of Science, and Embase. During RME palatine suture opens and both halves of the maxilla separate from each other more anteriorly than posteriorly. The maxillary centre of rotation in the horizontal plane is in the area of pterygoid processes. From the frontal view the separation of the maxilla halves has a shape of a triangle with a base running caudally, and an apex in the area of nasal bones; both parts of the maxilla rotate also transversally. When discussing sagittal and vertical changes, some authors report the movement of the maxilla forward and down, others proved also backward movement, or they reject vertical changes in the position or the maxilla movement. A number of studies confirmed posteriorotation of the palatal plane and the whole maxilla. The results of the works published are often significantly different. The problem of the effect of RME on the maxilla skeleton is not clear-cut and simple.
Keywords: Maxilla; lidé; maxila; techniky palatinální expanze; Palatal Expansion Technique; Treatment Outcome; výsledek terapie; Humans